THE SYSTEM OF TEMPERATURE AND WATER PH MONITORING AND CONTROL ON AROWANA FISH FARM BREEDING (SCLEROPAGES FORMOSUS) USING IOT BASED FARM AQUACULTURE - Agus, Agus; Suryadiputra Liawatimena; Joshua Jenriwan L Tobing; Rahmanda Arie Purnomo (Media Bina Ilmiah, 2023)
This research was conducted in December 2022 arowana fish property PT. Aquafam Jaya Lestari in cultivation, Riau Province. It was aimed to designinternet of things technology that expected to help arowana fish farmer in monitoring and controlling more effectively and practically. The method used for this research is case study and respondents were taken is the arowana farmer.In monitoring arowana fish water quality, most farmers still adopt traditional farming models that rely too much on experience, which cannot make scientific judgments on water quality and environmental changes. UsingArduino, LoRa, cellular technology and integrate with a variety of sensors and automatic devices (for example: temperature sensor, pH sensor, water pump, selenoid, aerator), it provides a smart solution for water quality monitoring to create tightly controlled and sustainable growth conditions. The system changes all the time to collect the data of temperature and pHand automatically adjust the temperature and pH to best treatment that pH range 6.5 – 7.5 and temperature 26 – 30°C . The final result of this research is analisys data by comparing 3 treatments on arowana with different pH and temperature.Observation result shows that the treament with pH range 6.5 – 7.5 and temperature 26 – 30°Cthe fish will provide an optimum response to the feed so that growht well and faster and will be able to produce optimally